(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the influence of social media on the mental health of adolescents and young adults from both theoretical and empirical perspectives. Social media has become a pervasive part of young people’s daily lives, shaping their social interactions, self-perception, and emotional well-being. The study highlights key psychological mechanisms through which social media use affects mental health, including social comparison, online peer feedback, identity formation, and exposure to cyberbullying. Furthermore, the article presents empirical findings on the relationship between social media engagement and outcomes such as anxiety, depression, self-esteem, and emotional regulation. A scientific table summarizes core psychological determinants, followed by a detailed discussion of their implications. The findings suggest that responsible social media use, digital literacy, and psychological interventions are crucial for promoting healthy psychosocial development among youth.